Ultrasonic power measurement by Kibble balance. (15th November 2022) - Mayworm, R.C.; Webster, E.; Davidson, S.; Alvarenga, A.V.; Costa-Felix, R.P.B.
Highlights: Ultrasound power is a crucial quantity for medical applications. Kibble balance is a novel approach to measure mass and related quantities. Using a Kibble balance to measure ultrasonic power avoids the need for knowing the local gravity. Uncertainty budgets for high power (>10 W) is even better than conventional radiation force balance. The results may be used directly allow high ultrasound power with relatively low uncertainty. Abstract: In May 2019, the International System of Units (SI) was revised. The new SI outlines the measurement system that allows the realisation of the kilogram using the Kibble balance. This work aims to develop and use a bench-top Kibble balance to perform ultrasonic power measurements, which are currently performed by a conventional balance. When replacing the traditional balance with a Kibble balance, the local gravity acceleration, one of the variables for measuring the ultrasonic power, is nullified, allowing the ultrasonic power to be measured in any place of the earth, without the need to know the value of the acceleration of the gravity. A low-cost bench-top Kibble balance was built using a 3D printer, a Raspberry microcomputer, an oscilloscope, and Python programming language. The prototype developed was able to measure a radiation power range from 1.4 W to 21.7 W and it obtained uncertainties lower than 5 % for the range above 9.6 W. Therefore, it is concluded that the developed system presented satisfactory results, especially considering that the system was built from a 3D printer. It is proposed that the system can be used as a basis for the development of new ultrasonic power measurement systems using the Kibble balance method.